COLONIAL CAPITAL AND DEVELOPMENT OF COFFEE PLANTATIONS IN TRAVANCORE - Lekha Rani.M.L
Coffee was the first among the plantation crops imported into India and into Travancore. The climate and the soil of Travancore were found to be perfect for coffee plantation. It was the chief crop of the planting districts of Travancore. The present study is an attempt to trace the development of coffee plantations in Travancore. The specific focus on Travancore is useful because it allows an analysis of the relationship between this formally independent state and colonial rulers. Historically the beginnings of coffee plantations in Travancore were a product of colonialism.